Voting with interdependent values: The condorcet winner - Alex Gershkov; Andreas Kleiner; Benny Moldovanu; Xianwen Shi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
We generalize the standard, private values voting model with single-peaked preferences and incomplete information by introducing interdependent preferences. Our main results show how standard mechanisms that are outcome-equivalent and implement the Condorcet winner under complete information or under private values yield starkly different outcomes if values are interdependent. We also propose a new notion of Condorcet winner under incomplete information and interdependent preferences, and discuss its implementation. The new phenomena in this paper arise because diffrent voting rules (including dynamic ones) induce different processes of information aggregation and learning.
Keywords: 330